Ectopic ATP synthase in endothelial cells: a novel cardiovascular therapeutic target - Fu, Yi; Zhu, Yi (Current pharmaceutical design, 2010)
Adenosine triphosphate (ATP) synthase produces ATP in cells and is found on the inner membrane of mitochondria or the cell plasma membrane (ectopic ATP synthase). Here, we summarize the functions of ectopic ATP synthase in vascular endothelial cells (ECs). Ectopic ATP synthase is involved in adenosine metabolism on the cell surface through its ATP generation or hydrolysis activity. The ATP/ADP generated by the enzyme on the plasma membrane can bind to P2X/P2Y receptors and activate the related signalling pathways to regulate endothelial function. The β-chain of ectopic ATP synthase on the EC surface can recruit inflammatory cells and activate cytotoxic activity to damage ECs and induce vascular inflammation. Angiostatin and other angiogenesis inhibitors can have anti-angiogenic functions by inhibiting ectopic ATP synthase on ECs. Moreover, ectopic ATP synthase on ECs is a receptor for apoA-I, the acceptor of cholesterol efflux, which implies that endothelial ectopic ATP synthase is involved in cholesterol metabolism. Coupling factor 6 (CF6), a part of ectopic ATP synthase, is released from ECs and can inhibit prostacyclin synthesis and promote nitric oxide (NO) degradation to enhance NO bioactivity. Because ATP/ADP generated by ectopic ATP synthase can induce NO production, substances such as CF6 can inhibit NO generation by inhibiting surface ATP/ADP production. Thus, the components of ectopic ATP synthase are associated with regulation of vascular tone. Through these functions, ectopic ATP synthase on ECs is considered a potential and novel therapeutic target for atherosclerosis, hypertension and lipid disorders.